Management of ufra disease of rice caused by Ditylenchus angustus with nematicides and resistance - Latif, Mohammad Abdul; Ullah, Md Wali; Yusop, Mohd Rafii; Tajul, Mohammad Islam (Academic Journals, 2011)
The effects of nematicide application timing and type on the management of ufra disease of rice caused by Ditylenchus angustus were investigated in the rain-fed and irrigated rice ecosystems. A broad range of rice (Oryza sativa L.) genotypes were also screened for resistance to D. angustus. Ufra infestation was significantly reduced when 1 kg ai/ha furadan 5G was applied up to 20 d before transplanting of infested seedlings in the field. Three granular nematicides, sunfuran 5G, edfuran 5G and forwafuran 5G, all applied at 1 kg ai/ha were evaluated against ufra in comparison with 1 kg ai/ha furadan 5G and a nontreated control. In both the ecosystems, all the 3 nematicides significantly reduced the number of damaged-tillers and total ufra infestation compared to the non-treated control. Similarly, sunfuran 5G, edfuran 5G, and forwafuran 5G treated plots had 45.3 to 52.7% healthy panicles with 3.89 to 4.02 t/ha yield in rain-fed rice and 47.6 to 53.0% healthy panicles with 3.85 to 3.97 t/ha yield in rain-fed and irrigated rice, respectively. These yields were similar to furadan-treated rice in 2 ecosystems. Yield losses due to ufra disease were 49.1 and 42.4% in the rain-fed and irrigated rice, respectively. Soil application of the nematicides, forwafuran, edfuran and sunfuran was cost-effective especially in fields of endemic areas. A total of 53 rice entries were tested, only 4 entries, fukuhonami, hyakikari, akiyu taka and matsuhonami showed highly resistance reactions to D. angustus.